MANAJEMEN PELAYANAN : USAHA UNTUK MENINGKATKAN KUALITAS PELAYANAN - Ruhana, Ika (Profit: Jurnal Adminsitrasi Bisnis, 2007)
A-high qualified service is a crucial problem to be solved now. The change of service paradigm from bureaucrat-oriented to society oriented should be followed with a change in the working culture reflected in customer-oriented attitude and behavior.Customer want a cheaper, better, faster, newer, and simpler service could be realized. Service management is a responsibility of every level management and employee to improve customer satisfaction. There are four activities in service management to increase service quality : planning service that costumer needs; processing data; giving service; and respecting costumer complaint. Finally, better service management can be used to increase service quality